Chimeric antigen receptor engineered NK cellular immunotherapy overcomes the selection of T-cell escape variant cancer cells. Issue 3 (19th March 2021) - Lee, Maxwell Y; Robbins, Yvette; Sievers, Cem; Friedman, Jay; Abdul Sater, Houssein; Clavijo, Paul E; Judd, Nancy; Tsong, Edward; Silvin, Chris; Soon-Shiong, Patrick; Padget, Michelle R; Schlom, Jeffrey; et al.
Abstract : Background: As heterogeneous tumors develop in the face of intact immunity, tumor cells harboring genomic or expression defects that favor evasion from T-cell detection or elimination are selected. For patients with such tumors, T cell-based immunotherapy alone infrequently results in durable tumor control. Methods: Here, we developed experimental models to study mechanisms of T-cell escape and demonstrated that resistance to T-cell killing can be overcome by the addition of natural killer (NK) cells engineered to express a chimeric antigen receptor (CAR) targeting programmed death ligand-1 (PD-L1). Results: In engineered models of tumor heterogeneity, PD-L1 CAR-engineered NK cells (PD-L1 t-haNKs) prevented the clonal selection of T cell-resistant tumor cells observed with T-cell treatment alone in multiple models. Treatment of heterogenous cancer cell populations with T cells resulted in interferon gamma (IFN-γ) release and subsequent upregulation of PD-L1 on tumor cells that escaped T-cell killing through defects in antigen processing and presentation, priming escape cell populations for PD-L1 dependent killing by PD-L1 t-haNKs in vitro and in vivo. Conclusions: These results describe the underlying mechanisms governing synergistic antitumor activity between T cell-based immunotherapy that results in IFN-γ production, upregulation of PD-L1 on T-cell escape cells, and the use of PD-L1 CAR-engineered NK cells to target and eliminate resistant tumor cell populations.